Pediatric Gastroenterology Research - Vasile Valeriu Lupu; Ömer Faruk Beşer; Simona Gurzu; Gabriela Stefanescu; Iuliana Magdalena Starcea; Anca Adam Raileanu; Alina Popp; Ancuta Lupu (Life, 2023)
For several decades, before the 19th century, pediatric pathology was considered to be an annex of adult pathology and treated as a secondary matter in medical practice [...]